Emendas parlamentares no financiamento da Atenção Primária à Saúde: análise dos municípios do Cariri cearense - Maria Marcleide do Nascimento; Maria Nizete Tavares Alves; Karla Denise Barros Ribeiro Vasques; Amanda Cordeiro de Oliveira Carvalho; Maria de Fátima Vasques Monteiro (Revista ft, 2026)
The study analyzes the mobilization and distribution of financial resources originating from parliamentary amendments allocated to the financing of Primary Health Care in the municipalities of the Crato Health Microregion, in the Cariri region of Ceará. This is an ecological study with a quantitative approach and a descriptive-analytical nature, based on secondary data from the National Council of Municipal Health Secretariats and the Transparency Portal of the Office of the Comptroller General, referring to the period from 2019 to 2023. The analysis is grounded in the theoretical framework of Collective Health concerning financing, equity, and governance of the Unified Health System. The results indicate that parliamentary amendments have acted as a relevant complementary mechanism in the financing of PHC, especially for increasing funding through the Primary Care Floor and the Basic Care Floor. Heterogeneity was observed in the distribution of resources among municipalities, with concentration in territories with greater political-institutional capacity, highlighting limitations regarding equity, predictability, and medium- and long-term planning. It is concluded that, although they expand municipal response capacity, parliamentary amendments have a predominantly compensatory character.